Climbing beans reach new heights - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Improved varieties of climbing beans are being developed jointly by scientists at the Insitut des Sciences Agronomiques do Rwanda and their counterparts at the International Center for Tropical Agriculture (CIAT), both at its headquarters in...